Systematic review and narrative synthesis of the impact of Appreciative Inquiry in healthcare. Issue 2 (16th June 2022) - Merriel, Abi; Wilson, Amie; Decker, Emily; Hussein, Julia; Larkin, Michael; Barnard, Katie; O'Dair, Millie; Costello, Anthony; Malata, Address; Coomarasamy, Arri
Abstract : Background: Appreciative Inquiry is a motivational, organisational change intervention, which can be used to improve the quality and safety of healthcare. It encourages organisations to focus on the positive and investigate the best of 'what is' before thinking of 'what might be', deciding 'what should be' and experiencing 'what can be'. Its effects in healthcare are poorly understood. This review seeks to evaluate whether Appreciative Inquiry can improve healthcare. Methods: Major electronic databases and grey literature were searched. Two authors identified reports of Appreciative Inquiry in clinical settings by screening study titles, abstracts and full texts. Data extraction, in duplicate, grouped outcomes into an adapted Kirkpatrick model: participant reaction, attitudes, knowledge/skills, behaviour change, organisational change and patient outcomes. Results: We included 33 studies. One randomised controlled trial, 9 controlled observational studies, 4 qualitative studies and 19 non-controlled observational reports. Study quality was generally poor, with most having significant risk of bias. Studies report that Appreciative Inquiry impacts outcomes at all Kirkpatrick levels. Participant reaction was positive in the 16 studies reporting it. Attitudes changed in the seventeen studies that reported them. Knowledge/skills changed in the 14 studies that reported it, although in one it was not universal. Behaviour change occurred in 12 of the 13 studies reporting it. Organisational change occurred in all 23 studies that reported it. Patient outcomes were reported in eight studies, six of which reported positive changes and two of which showed no change. Conclusion: There is minimal empirical evidence to support the effectiveness of Appreciative Inquiry in improving healthcare. However, the qualitative and observational evidence suggests that Appreciative Inquiry may have a positive impact on clinical care, leading to improved patient and organisational outcomes. It is, therefore, worthy of consideration when trying to deliver improvements in care. However, high-quality studies are needed to prove its effects. PROSPERO registration number: CRD42015014485.